PENDEKATAN QUR'ANI DALAM MENJAGA KESEHATAN MENTAL SISWA - Nofita Rahmawati, Roro Kurnia (CV. Jendela Gagasan, 2025)
This study examines the Qur'anic approach to maintaining students' mental health in the educational context. Against the backdrop of increasing mental health issues among students, this research aims to identify mental health principles in the Qur'an, formulate an applicable intervention model, and measure its effectiveness. Using qualitative library research methodology, this study analyzes relevant literature on Islamic perspectives on mental health. The findings reveal eight fundamental Qur'anic principles for mental health: fitrah, tazkiyatun nafs, tawakkal, qana'ah, sabar, istiqamah, ukhuwah, and dzikr. The proposed intervention model integrates these principles into four components: curriculum development, educator training, student mentoring programs, and family-community involvement. Longitudinal evaluation demonstrated significant improvements in students' psychological resilience, emotional regulation, interpersonal relationships, spiritual well-being, and academic performance, with decreased anxiety, depression, and stress symptoms, providing evidence for the effectiveness of the Qur'anic approach.